2001
DOI: 10.1108/00070700110383154
|View full text |Cite
|
Sign up to set email alerts
|

McDonald’s: “think global, act local” – the marketing mix

Abstract: Focuses on the marketing mix of McDonald’s. Highlights how the company combines internationalisation and globalisation elements according to various fast food markets. Using the effect of strategical and tactical models, the case illustrates the effect of McDonald’s on the global environment and how they adapt to local communities. Describes future franchise plans for McDonald’s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 7 publications
1
37
0
7
Order By: Relevance
“…It has penetrated international markets through the development of scientific management techniques alongside and the adaptation of its offerings to local contexts (Vignali, 2001). Although the standard menu offers many signifiers of American "home", such as the fried apple pie (Willink, 2006), the company's policy is to customise restaurants to local needs, for example, replacing pork with lamb in Muslim countries (cf.…”
Section: Mcdonald's: a Foodservice Operation And Global Brandmentioning
confidence: 99%
See 1 more Smart Citation
“…It has penetrated international markets through the development of scientific management techniques alongside and the adaptation of its offerings to local contexts (Vignali, 2001). Although the standard menu offers many signifiers of American "home", such as the fried apple pie (Willink, 2006), the company's policy is to customise restaurants to local needs, for example, replacing pork with lamb in Muslim countries (cf.…”
Section: Mcdonald's: a Foodservice Operation And Global Brandmentioning
confidence: 99%
“…Although the standard menu offers many signifiers of American "home", such as the fried apple pie (Willink, 2006), the company's policy is to customise restaurants to local needs, for example, replacing pork with lamb in Muslim countries (cf. Kabbassi, 2008;Kamalipour, 2006;Vignali, 2001;Watson, 1997).…”
Section: Mcdonald's: a Foodservice Operation And Global Brandmentioning
confidence: 99%
“…Other research investigated factors influencing the brand perception of fast food outlets by consumers from different countries, such as the USA, India, Malaysia, Pakistanetc [1] [18] [19]. According to previous research focusing on fast food branding [3] [18] [20], there are two main arguments why a strong brand identity is of key influence for market success: 1) a strong brand image can create a competitive advantage which is more difficult to copy than functional aspects; 2) the brand image reduces the risk of being perceived as a commodity and assist consumers in quickly developing expectations (and preferences) about this brand. Thus, building a well-accepted brand seems to be a key factor for fast food products to successfully enter the market.…”
Section: Relevance Of Food Brandsmentioning
confidence: 99%
“…McDonald's is the brand studied most frequently-not only because of its prevalence [1] [19] [20], but also due to its background as the world's major fast food advertiser. Thus, we compared McDonalds with two types of (hypothetical) novel brands: an imaginary novel global brand "FastyJu" and an imaginary novel local brand "Тинар" (Tinar), the latter written in Cyrillic alphabet.…”
Section: Vignettes Used For Revealing Consumers' Perceptionsmentioning
confidence: 99%
“…[3] other people examined the criteria of marketing mix and considered those criteria for different times . [4]. But as regards to all studies and research which have been done, it can be observed that the only criteria which is expressed and estimated in all studies and research is marketing mix (4Ps).…”
mentioning
confidence: 99%